Endometrial and peritoneal expression of aromatase, cytokines, and adhesion factors in women with endometriosis - Kyama, Cleophas M.; Overbergh, Lutgart; Mihalyi, Attila; Meuleman, Christel; Mwenda, Jason M.; Mathieu, Chantal; D'Hooghe, Thomas M. (Fertility and sterility, 2008)
To examine messenger (m) RNA expression of aromatase, cytokines, and adhesion factors in women with and without endometriosis. Patients with endometriosis were compared with control patients. University Hospital Gasthuisberg, Leuven, Belgium. A total of 35 patients who had laparoscopic surgery during the luteal phase (n = 20) or the menstrual phase (n = 15) were selected for this study based on cycle phase and presence/absence of endometriosis. Tissues of endometrium and macroscopically normal peritoneum were collected during hysteroscopy and laparoscopic surgery, respectively, from 24 women with revised American Society for Reproductive Medicine stage (rASRM) stages I–II (n = 12) and III–IV (n = 12) endometriosis and 11 control patients with normal pelvises. Tissue samples were selected from a tissue bank, based on the phase of the cycle (menstrual or luteal) and the presence/absence of endometriosis. The mRNA levels of aromatase, vimentin, vascular cell adhesion molecule 1 (VCAM-1), α V and β 3 integrins, interleukin (IL)-1β, regulated on activation normal T-cell expressed and secreted (RANTES), and monocyte chemotactic protein 1 (MCP-1) were evaluated using real-time reverse transcriptase polymerase chain reaction. During menstrual phase, increased endometrial mRNA levels of α V integrin, combined α Vβ 3 integrins, and increased peritoneal IL-1β mRNA levels—but decreased peritoneal MCP-1 mRNA levels—were observed in women with endometriosis compared with control subjects. During luteal phase, endometrial mRNA levels of IL-1β and RANTES were increased in women with endometriosis compared with control subjects. Endometrial aromatase mRNA expression was higher in women with endometriosis than in control subjects in combined phases. Women with endometriosis had increased peritoneal mRNA expression of RANTES and VCAM-1 during menstrual compared with luteal phase. Aberrant mRNA expression of aromatase, cytokines, and adhesion factors in endometrium and peritoneum suggests that both tissues are involved in the pathogenesis of endometriosis.